Parental choice education - Johnson, Daphne (London : UNWIN HYMAN, 1990)
This is a comprehensive review of major research into parental choice in the light of the 1988 Education Reform Act. This book examines the immediate and long term effects of choice on schools, local authorites, parents and children. The author focuses paricularly on the kinds of choices that the introduction of the new city technology colleges and the grant-maintained schools have offered and points out that the changed relationship between public and private schools has led to the necessity of their competing more directly than before. She also assesses research into the effects of the Assisted Places Scheme.
Includes bibliographical references.
Keywords: School choice -- England; Education -- England; Education and state -- Great Britain; Education -- Great Britain